Two methods for tree volume estimation of Acacia melanoxylon in Portugal - Rucha, Andreia (2011)
Two models were developed to evaluate total volume under and over-bark of Blackwood (Acacia melanoxylon R. Br.) stand trees. By variance analysis regarding volume with and without bark it was confirmed that trees age is responsible for 48 to 50% of its volumetric behaviour. Considered the averages of those variables and regarding the three homogeneous groups of the studied sites, a single model type was used (v=β1dβ2hβ3) for estimating volumes. The critical errors are between 72 and 195 dm3 under-bark, and 82 and 212dm3 over-bark. The model that uses sites as dummy variables to the estimation of stand tree volumes is the same, and this method performs maximum expected errors with values of 155 dm3 (under-bark) and 169dm3 (over-bark), to mean maximum volumes of 1362 and 1459 dm3 respectively. The use of dummy variables is a more expedite and rapid modelling method, and its maximum expected errors perform lower values.